2004
DOI: 10.1016/s1074-7613(04)00079-2
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Competitiveness of Autoantigen-Engaged B Cells due to Increased Dependence on BAFF

Abstract: Peripheral autoantigen binding B cells are poorly competitive with naive B cells for survival and undergo rapid cell death. However, in monoclonal Ig-transgenic mice lacking competitor B cells, autoantigen binding B cells can survive for extended periods. The basis for competitive elimination of autoantigen binding B cells has been unknown. Here we demonstrate that autoantigen binding B cells have increased dependence on BAFF for survival. In monoclonal Ig-transgenic mice, each autoantigen binding B cell recei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

30
454
3
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 520 publications
(488 citation statements)
references
References 79 publications
30
454
3
1
Order By: Relevance
“…We speculate that a B cell SAg more commonly delivers a very strong BCR signal that is associated with greater cellular requirements for cytokine or cognate help that are critical for survival and/or cell cycle progression, as well as because a SAg also enhances cellular competition among the great numbers of B cells affected by this BCRtargeted ligand (3). This model is consistent with our demonstration that supraphysiological levels of BAFF can inhibit both the BCR-mediated up-regulation of Bim and subsequent apoptotic death akin to other systems (11,12,14). This model is also supported by our recent findings that relatively larger SAg doses induce limited proliferation with more rapid and larger scale death, presumably due to the more rapid exhaustion of available prosurvival signals (7).…”
Section: E and F)supporting
confidence: 91%
See 1 more Smart Citation
“…We speculate that a B cell SAg more commonly delivers a very strong BCR signal that is associated with greater cellular requirements for cytokine or cognate help that are critical for survival and/or cell cycle progression, as well as because a SAg also enhances cellular competition among the great numbers of B cells affected by this BCRtargeted ligand (3). This model is consistent with our demonstration that supraphysiological levels of BAFF can inhibit both the BCR-mediated up-regulation of Bim and subsequent apoptotic death akin to other systems (11,12,14). This model is also supported by our recent findings that relatively larger SAg doses induce limited proliferation with more rapid and larger scale death, presumably due to the more rapid exhaustion of available prosurvival signals (7).…”
Section: E and F)supporting
confidence: 91%
“…In fact, B cells from SpA-treated Bimdeficient mice displayed enhanced responses to stimulation with the B cell mitogens, LPS, or anti-IgM (i.e., IgG F(abЈ) 2 ), or CD40 ligand, compared to those from control-treated mice (data not shown). Hence, B cells surviving from SpA exposure are not commonly anergic (12) and, under the conditions evaluated, Bim-deficient B cells instead displayed enhanced responsiveness to restimulation, which is consistent with evidence from other systems that Bim may contribute to non-deletional negative selection mechanisms (i.e., anergy) (12,14).…”
Section: E and F)supporting
confidence: 85%
“…Recently, it was shown that Sle3/5 impacts IgH CDR3 sequences, somatic mutations, and receptor editing, although it remains uncertain whether these effects are extrinsic and/or intrinsic (39). Cultured B6.Sle3/5 bone marrow-derived DCs have been found to display high gene expression of BAFF/BLyS (40), which has been shown to rescue autoreactive B cells from apoptosis (41,42). This cytokine might be one contributor to the extrinsic effect of Sle3/5 on autoreactive B cells.…”
Section: Discussionmentioning
confidence: 99%
“…This has been tested in experiments using the HEL/anti-HEL double transgenic model (Lesley, Xu et al 2004;Thien, Phan et al 2004), and in our recent collaborative studies using the 3H9 transgenic model of dsDNA autoreactivity (Hondowicz, et al, submitted). Together, these studies show that the likelihood of autoreactive clonotypes being eliminated at the transitional stage is determined by the availability of BLyS and the degree of competition from other, concomitantly emerging clonotypes.…”
Section: Homeostatic Demands Control B Cell Survival and Selectionmentioning
confidence: 99%